Performance of the graduates of the revised Bachelor of Science in Nursing (BSN) curriculum according to selected indicators as perceived by the nurse managers and nurse graduates of selected hospitals in Cagayan De Oro City 1992-1993 - Palad, Ramona Heidi C.
This study was an attempt to determine the performance of the graduates of the Revised Bachelor of Science in Nursing Curriculum as perceived by the nurse graduates and nurse managers of selected hospitals in Cagayan De Oro City according to selected indicators. Specifically, this study was limited to the following aspects of the problem: 1. What is the profile of the respondents in this study as outlined below: 1.1 age 1.2 place of school graduated from 1.3 highest educational attainment 1.4 area of assignment 1.5 nursing experience in years 2. How do the 2 groups of respondents perceive the performance of the graduates of the Revised Bachelor of Science in Nursing Curriculum according to the following indicators: 2.1 utilization of the nursing process in patient's care 2.2 interpersonal relations 2.3 utilization of management skills in health care setting 2.4 utilization of research findings in the care of clients 2.5 personal and professional development 3. How do the nurse graduates of the Revised BSN Curriculum compare in their performance rating considering the average of both the self and the nurse manager's evaluation when grouped according to the following: 3.1 age 3.2 place of school graduated from 3.3 area of assignment 3.4 nursing experience in years 4. What are the comments and observations of the 2 groups of respondents on the performance of the graduates of the Revised Bachelor of Science in Nursing Curriculum. The subjects of the study were 47 nurse managers and 110 nurse graduates of the Revised BSN Curriculum to whom the questionnaire was administered. The study was conducted in 6 selected hospitals of Cagayan De Oro City namely: Army Station Hospital, Cagayan Medical Center, J. R. Borja Memorial Hospital, Madonna and Child Hospital, Maria Reyna Hospital and the Northern Mindanao Regional Training Hospital. The descriptive survey method was used in the study. Likewise, the following tools were used: 1) Questionnaire for the nurse managers, and 2) Questionnaire for the nurse graduates. Various statistical procedures were used to treat and analyze the data namely: Descriptive statistics such as mean, percentages and standard deviation. T-test for comparison of means between 2 groups of respondents; and F-test for comparison of means between 3 or more groups of respondents.